Can analysts see through goodwill bubbles? The impact of goodwill on analysts' forecasts - Shuang Xue; Peiji Xu (China Journal of Accounting Studies (CJAS), 2021)
In recent years, the amount of goodwill has been increased dramatically and become one of the difficult problems in academic and accounting practice. This paper focuses on the impact of goodwill on analysts' forecasts. It is found that goodwill can increase the optimism and decrease the accuracy of analysts' forecasts because of its low quality. Goodwill recognised initially in bull market or from the M&A without founder-chairman or founder-CEO contains more bubbles and tends to be lower quality. The more the bubbles, the larger the optimism or the errors of analysts' forecasts. In order to exclude the alternative explanations, we also, respectively, take cross-sectional tests to control the number of analysts, the number of star analysts, and whether there is M&A in year t, and then further examine the dynamic changes between goodwill and analysts' forecasts.
Keywords: 650; Goodwill; goodwill bubble; analysts' forecast; bull and bear market; foundermanagement